Evaluation of the dislodgement force of splinted restorations with engaging conical abutments over multiple nonparallel implants (in-vitro study) - Mohamed Moataz Khamis; Niveen Hazem Zakaria; Khaled Mohamed Farrag; Salma Abolgheit (BMC, 2023)
Abstract Background Splinted multiunit cement-retained restorations with screw access channels over engaging abutments are viable implant prosthetic options. However, information regarding the maximum degree of divergence between multiple implants is lacking. The purpose of this in vitro study was to determine the maximum degree of divergence between 2 adjacent implants with conical connections that allows insertion and removal of splinted restorations with engaging preparable abutments or titanium base abutments. Methods Two implants were aligned in a stone base, one straight and the other at an angle ranging from 0 to 20 degrees. The implants represented an implant system that had an internal conical connection and a hexed abutment engaging the base of the connection. Two straight preparable engaging cement retained abutments were screwed onto the implants and splinted together using acrylic resin. A total of 11 angles were tested, with 7 specimens for every angle. Evaluation of dislodging force was performed by pulling out the splinted abutments after unscrewing them. This was performed subjectively by 3 blinded investigators who applied a tactile pulling force. A scale of 0-10 was used to estimate the pulling force. Objectively the dislodging force was measured in Newtons using a universal testing machine. A statistical correlation was made between the subjective and objective dislodging force values using Spearman's rank correlation coefficient. Results The mean subjective values increased gradually from 0 to 16 degrees. A sudden rise was noticed at 18 degrees (9.71 ± 0.23) and, at 20 degrees, the investigators were not able to remove the splinted abutments from the implants. The mean objective dislodgement force values increased gradually from 0 to16 degrees and abruptly from 16 degrees (13.57 ± 0.45 N) to 18 degrees (25.40 ± 0.66 N) and 20 degrees (35.22 ± 0.64). The correlation between the subjective and the objective evaluations assessed using the Spearman's rank correlation coefficient was 0.98 indicating a statistically significant correlation (P < .001). As the objective dislodging force increased, the subjective dislodgement difficulty increased. Conclusions Splinting cement retained restorations with screw access channels on engaging abutments is possible when multiple implants with conical connections having an internal flare angle of 8 degrees are used, with implant divergence of up to 16 degrees.